THE INTERPRETATION OF AULIYĀ CONTEXTUAL MEANING IN THE QUR’AN (STUDY OF C.S PEIRCE SEMIOTICS THEORY) - Fatimah, Fatimah; Lutfiah, Winona (Jurnal Adabiyah, 2021)
The term auliyā’ is usually interpreted by the community as the leader, this is supported by interviews conducted by the researchers as well as the reports regarding the change in the meaning of auliyā in surah al-Maidah verse 51 by the Ministry of Religion from ’leader’ to ’friend’ which was again widely discussed at the beginning of June 2021. The narrow understanding of the auliyā term which is allowed to continue has implications for the reduction of the meaning of the Qur’an. Therefore, this study aims to discuss the interpretation of the differentiation of the auliyā’ term meaning contextual in the Qur’an based on a semiotic study ; Charles Sanders Peirce. This study used qualitative text analysis methods, especially qualitative content analysis in analyzing the available data. By using the Semiotics approach, this study interpreted the term Auliyā’ using the tracheotomy theory of C.S. Peirce. The results of this study indicated that the interpretation of the term auliyā’ was not only limited to the leader but was also interpreted as a helper, protector, friend, lover, master, and guardian. This study recommends to academics to develop further the substance of research in addition, this research is also expected to be additional information for readers that the term auliyā’ is not only limited to the meaning of leader so the judgmental attitudes that caused the reduction of the meaning of the Qur’an no longer occurred. الملخص عادة ما يفسر المجتمع مصطلح الأولياء على أنه زعيم فقط ، ويدعم ذلك المقابلات التي أجراها المؤلف وكذلك الأخبار المربكة فيما يتعلق بالتغيير في معنى الأولياء في سورة المائدة الآية 51 من قبل وزارة الدين من. "القائد" إلى "الصديق" الذي نوقش مرة أخرى على نطاق واسع في البداية. يونيو 2021. إن الفهم الضيق لمصطلح الأولياء الذي يُسمح له بالاستمرار له آثار على تقليل معنى القرآن، وبالتالي، تهدف هذه الدراسة لمناقشة تفسير التفريق بين مصطلح "الأولياء" المعنى السياقي في القرآن بناءً على دراسة السيميائية تشارلز ساندرز بيرس. تستخدم هذه الدراسة أساليب التحليل النوعي للنص ، وخاصة تحليل المحتوى النوعي في تحليل البيانات المتاحة. باستخدام منهج السيميائية، تفسر هذه الدراسة مصطلح أولياء باستخدام نظرية تريكوتومي في سي. بيرس. تشير نتائج هذه الدراسة إلى أن تفسير مصطلح الأولياء لا يقتصر على القائد فحسب، بل يتم تفسيره أيضًا على أنه مساعد، وحامي، وأصدقاء، ومحب، وسيد، ووصي. توصي هذه الدراسة الأكاديميين بمزيد من تطوير مادة البحث بالإضافة إلى ذلك، من المتوقع أيضًا أن يكون هذا البحث معلومات إضافية للقراء أن مصطلح الأولياء لا يقتصر فقط على معنى القائد، وبالتالي فإن المواقف القضائية التي تؤدي إلى تقليل لم يعد معنى القرآن موجودًا.